In vivo quantification of superficial cortical veins on susceptibility-weighted imaging with artificial intelligence image segmentation and the potential mechanism of human cognitive decline - Xie, Qi; Xu, Hai-Xia; Wang, Ya-Jie; Chen, Hui-Xian; Tu, Xiao-Fang; Han, Peng-Peng; Wu, Jun (Frontiers in Aging Neuroscience, 2025)
ObjectiveChanges in superficial cerebral veins (SCV) caused by different cognitive levels were observed using MR susceptibility-weighted imaging (MR-SWI) to explore the vascular mechanism underlying human brain aging and potential biomarkers of cognitive decline in vivo.MethodsThree hundred and sixty-four participants (184 males,180 females and aged 18–79 years) were included in this study. The quantitative features of SCVs in the cerebral hemispheres were collected via MR-SWI and were processed with an artificial intelligence (AI) image segmentation algorithm. The changes in the morphology and structure of the SCVs were analyzed with SPSS software.ResultsThe quantitative value of SCV were significantly greater in males than in females. In higher age groups, the total number of SCVs and the number of SCVs in the left and right cerebral hemispheres significantly decreased. The number of SCVs in hypertensive patients was significantly lower than that in non-hypertensive patients. Additionally, the diameter, curvature and length of SCVs in the right cerebral hemispheres were significantly lower in anemic patients than in non-anemic patients. The number and length of SCVs in the bilateral cerebral hemispheres were negatively correlated with the rate of cognitive abnormalities. Among tea drinkers in the youth group, the number of SCVs in both hemispheres were negatively correlated with total tau protein (T-tau), and the curvature of SCVs in the right hemisphere was negatively correlated with phospho-tau181(P-tau181) and T-tau concentrations in venous blood. There was a negative correlation between the T-tau concentration in venous blood and tea consumption. The curvature of SCVs in the right cerebral hemisphere had a significant impact on cognitive decline, with a strong positive correlation. The length of SCV in the right hemisphere of the brain had a significant negative correlation with cognitive decline, however, this correlation was relatively weak.ConclusionThe quantitative value of SCV was negatively correlated with cognitive decline. Daily tea consumption may have a positive impact on the quantitative features of SCVs in the young group. As SCVs are a component of the glymphatic system, their blood flow may affect the clearance of toxic proteins.